PPAR-γ Promotes Hematoma Clearance through Haptoglobin-Hemoglobin-CD163 in a Rat Model of Intracerebral Hemorrhage - Gaiqing Wang; Tong Li; Shu-na Duan; Liang Dong; Xin-gang Sun; Fang Xue (Behavioural Neurology)
Background and Purpose. PPAR-γ is a transcriptional factor which is associated with promoting hematoma clearance and reducing neurological dysfunction after intracerebral hemorrhage (ICH). Haptoglobin- (Hp-) hemoglobin- (Hb-) CD163 acts as a main pathway to Hb scavenging after ICH. The effect of PPAR-γ on the Hp-Hb-CD163 signaling pathway has not been reported. We hypothesized that PPAR-γ might protect against ICH-induced neuronal injury via activating the Hp-Hb-CD163 pathway in a rat ICH model. Methods. 107 Sprague-Dawley rats were used in this research. They were randomly allocated to 4 groups as follows: sham group, vehicle group, monascin-treated group, and Glivec-treated group. Animals were euthanized at 3 days after the model was established successfully. We observed the effects of PPAR-γ on the brain water content, hemoglobin levels, and the expressions of CD163 and Hp in Western blot and real-ime PCR; meanwhile, we measured hematoma volumes and edema areas by MRI scanning. Result. The results showed that PPAR-γ agonist significantly reduced hematoma volume, brain edema, and hemoglobin after ICH. It also enhanced CD163 and Hp expression while PPAR-γ antagonist had the opposite effects. Conclusions. PPAR-γ promotes hematoma clearance and plays a protective role through the Hp-Hb-CD163 pathway in a rat collagenase infusion ICH model.